Industry Payments to Urologists in 2014: an Analysis of the Open Payments Program. Issue 4 (July 2017) - Modi, Parth K.; Farber, Nicholas J.; Zavaski, Michael E.; Jang, Thomas L.; Singer, Eric A.; Chang, Steven L.
Abstract : Introduction: : Physician‐industry relationships are common in the U.S. and a source of considerable public scrutiny. The Open Payments program is a public database of all physician‐industry financial interactions in the U.S. administered by the Centers for Medicare & Medicaid Services. In this study we describe payments received by urologists for research and nonresearch purposes. Methods: : The number and value of payments to urologists were determined using Open Payments program data. The nature of each payment and identity of industry partners were analyzed. Descriptive statistics were calculated separately for research and nonresearch payment data. The total number of practicing physicians per specialty was obtained from the Association of American Medical Colleges Physician Specialty Data Book for 2014. Results: : In 2014, 8, 620 urologists had nonresearch financial relationships with industry for a total value of 32.4 million, with 2, 698 urologists receiving more than 1, 000 in total nonresearch payments. Urologists as a whole had the 8th highest total value received of all specialties. A total of 22.4 million was spent by industry for urology directed research funding, representing a small proportion of the more than 3 billion spent by industry on medical research in 2014. The majority (93.1%) of urology directed research funding was provided to nonteaching institutions. Conclusions: : The Open Payments program database is an important public database of financial transactions between industry and physicians. A large proportion of urologists received nonresearch related transfers of value from industry sources. Industry supported research funding is primarily awarded to nonteaching institutions.